Synthesis and Spectroscopic Characterization of Furan-2-Carbaldehyde-d - Jonas Jaster; Elias Dressler; Robert Geitner; Gregor Alexander Groß (Molbank, 2023)
Here, we present a protocol for the one-step synthesis of the title compound in quantitative yield using adapted Vilsmeier conditions. The product was characterized by 1H-,2H-,13C-NMR-, as well as IR and Raman spectroscopy. Spectral data are given in detail.